Analisis Investasi Sistem Penyediaan Air Bersih Kota Duri (Intake Air Baku Sungai Jurong II) - Halim, Donny; Siswanto, Siswanto; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This thesis aims to analyze the water supply system investment Duri city. City water needs spines increasing in line with population growth and urban growth. Currently the water supply held by PDAM, but its capacity can not meet all the needs of the citizens, to be sufficient, the water supply system needs to be developed, one of which is by way of searching for new sources of raw water. Source of raw water in the city is very limited capacity spines and long distances. Raw water sourced from Sungai Jurong II to supply raw water 140 liters/sec for PDAM Tirta Dharma Duri which is about 26 km. Analysis of investments in PDAM Tirta Dharma Duri performed by analyzing the use of the Net Present Value (NPV), Benefit Cost Ratio (BCR), Break Even Point (BEP) and Internal Rate Of Return (IRR) to determine the water supply system of investment and determine the price of water from the source of raw water to PDAM Tirta Dharma Duri IPA. The calculation of the price of raw water obtained before affixing is Rp. 981/m3.  Keywords : Analysis of investment, NVP, BCR, BEP, IRR and  the price of water.